Media Pembelajaran Peralatan Servis Sepeda Motor dengan Menerapkan Teknologi Augmented Reality - Miftahul Madani; Melati Rosanensi (Jurnal Teknologi Informasi dan Multimedia, 2025)
Learning media is one of the key components in the educational process. Teachers need to pay special attention to the use of learning media during teaching and learning activities. However, a lack of variety and suboptimal utilization of learning media often causes students to lose interest in learning. In fact, learning media aim to serve as tools to enhance the effectiveness of the learning process. Learning media are available in various forms, one of which is printed media or verbal explanation-based methods that are widely used in schools. This type of media is chosen for its practicality, adaptability to students' abilities, and ease of distribution. However, printed media have limitations, such as the inability to present elements like sound, animation, or three-dimensional objects. This study employs the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. The final product of this research is an application in ".apk" format that can be installed on Android devices. Augmented reality is a term used to describe various types of display technology that can add or integrate information in the form of text, symbols or graphics into the user's view of the real world, this application utilizes Augmented Reality technology to introduce motorcycle service tools, helping vocational high school (SMK) students acquire basic skills and access information via their smartphones. User testing using the Likert Scale resulted in a score of 33.46, which falls into the "Strongly Agree" category.